Hydrothermal Synthesis, Crystal Structure Determination, and Magnetic Properties of a New Calcium Iron Iridium Hydrogarnet Ca3(Ir2–xFex)(FeO4)2–x(O4H4)1+x with 0 ≤ x ≤ 1. Issue 8 (4th April 2019) - Poddig, Hagen; Hunger, Jens; Kamusella, Sirko; Klauss, Hans‐Henning; Wolter, Anja U. B.; Bastien, Gaël; Corredor Bohórquez, Laura T.; Doert, Thomas
Abstract : The new calcium iron iridium hydrogarnet Ca3 (Ir2– x Fe x )(FeO4 )2– x (H4 O4 )1+ x (0 ≤ x ≤ 1) was obtained by hydrothermal synthesis under strongly oxidizing alkaline conditions. The compound adopts a garnet‐like crystal structure and crystallizes in the acentric cubic space group I 4 3 d (no. 220) with a = 12.5396(6) Å determined at T = 100 K for a crystal with a refined composition Ca3 (Ir1.4 Fe0.6 )(FeO4 )1.4 (O4 H4 )1.6 . Iridium and iron statistically occupy the octahedrally coordinated metal position, the two crystallographically independent tetrahedral sites are partially occupied by iron. Hydroxide groups are found to cluster as hydrogarnet defects, i.e. partially substituting oxide anions around the empty tetrahedral metal sites. The presence of hydroxide ions was confirmed by infrared spectroscopy and the hydrogen content was quantified by carrier gas hot extraction; the overall composition was verified by energy dispersive X‐ray spectroscopy. The structure model is supported by 57 Fe‐Mössbauer spectroscopic data evidencing different Fe sites and a magnetic ordering of the octahedral iron sublattice at room temperature. The thermal decomposition proceeds via three steps of water loss and results in Ca2 Fe2 O5, Fe2 O3 and Ir. Mössbauer and magnetization data suggest magnetic order at ambient temperature with complex magnetic interactions. Abstract :